TRANSFORMATION OF THE INSURANCE COMPANY'S RESERVE MANAGEMENT SYSTEM UNDER THE INFLUENCE OF FINANCIAL DIGITALIZATION (INNOVATIVE ECONOMY, 2025)
Vodolazska O.A., Kyrychenko S.S. TRANSFORMATION OF THE INSURANCE COMPANY'S RESERVE MANAGEMENT SYSTEM UNDER THE INFLUENCE OF FINANCIAL DIGITALIZATIONPurpose. The aim of the article is to study the processes of transformation of the insurer's insurance reserve management system under the influence of financial digitalization, to identify the main trends, risks and prospects for the use of FinTech tools in the insurance market of Ukraine.Methodology of research. The research uses methods of analysis and synthesis to generalize theoretical approaches to the management of insurance reserves and determine the impact of financial digitalization on the activities of insurers. Comparative, structural and functional analysis made it possible to compare traditional and digital models of insurance reserve management and to identify their key differences. Findings. It is substantiated that financial digitization significantly changes traditional approaches to managing insurance reserves, providing a transition from static models to dynamic, risk-oriented and algorithmic solutions. A comparative description of traditional and digital models of insurance reserve management was conducted. It has been proven that the introduction of FinTech solutions, big data analytics, artificial intelligence and automated liquidity management systems contributes to increasing the accuracy of reserve calculations, optimizing the structure of assets, increasing liquidity and investment profitability. Originality. The theoretical and methodological provisions regarding the management of insurance reserves were further developed through the formation of the concept of digital transformation of reserves, which is based on the integration of artificial intelligence, algorithmic liquidity management and digital financial control. A generalized model of digital reserve management is proposed, taking into account the requirements of financial stability and regulatory oversight. Practical value. The obtained results can be used by insurance companies to improve the reserve management system, increase liquidity and competitiveness, as well as by regulatory authorities - to develop tools for digital financial supervision.Key words: insurance reserves, financial digitalization, insurance company, reserve management, FinTech, InsurTech, artificial intelligence, liquidity.
Keywords: insurance reserves; financial digitalization; insurance company; reserve management; FinTech; InsurTech; artificial intelligence; liquidity